NBAS variants are associated with quantitative and ualitative NK and B Cell deficiency - Lenz, Dominic; Pahl, Jens; Hauck, Fabian; Alameer, Seham; Balasubramanian, Meena; Baric, Ivo; Boy, Nikolas; Church, Joseph A.; Crushell, Ellen; Dick, Anke; Distelmaier, Felix; Gujar, Jidnyasa; et al. (Journal of clinical immunology, 2021)
Purpose  Biallelic pathogenic NBAS variants manifest as a multisystem disorder with heterogeneous clinical phenotypes such as recurrent acute liver failure, growth retardation, and susceptibility to infections. This study explores how NBAS-associated disease affects cells of the innate and adaptive immune system. - Methods  Clinical and laboratory parameters were combined with functional multi-parametric immunophenotyping methods in fifteen NBAS-deficient patients to discover possible alterations in their immune system. - Results  Our study revealed reduced absolute numbers of mature C D56dim natural killer (NK) cells. Notably, the residual NK cell population in NBAS-deficient patients exerted a lower potential for activation and degranulation in response to K562 target cells, suggesting an NK cell-intrinsic role for NBAS in the release of cytotoxic granules. NBAS-deficient NK cell activation and degranulation was normalized upon pre-activation by IL-2 in vitro, suggesting that functional impairment was reversible. In addition, we observed a reduced number of naïve B cells in the peripheral blood associated with hypogammaglobulinemia. - Conclusion  In summary, we demonstrate that pathogenic biallelic variants in NBAS are associated with dysfunctional NK cells as well as impaired adaptive humoral immunity.